HUBUNGAN TEKNOLOGI INFORMASI DAN FORMULASI STRATEGI PEMASARAN SERTA DAMPAKNYA TERHADAP KINERJA ORGANISASI - Sonjaya, Nana Supriatna; Yudianto, Agus; Nurpratama, Meddy (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The relationship between Information Technology and marketing strategy formulation has a significant impact on organizational performance. In the current digital era, Information Technology plays and has a very important role in collecting, storing and analyzing consumer data more efficiently. This allows organizations to better understand consumer behavior, preferences and market trends in greater depth. Using the data collected, organizations can design more focused and personalized marketing strategies, identifying the right market segments to target. By wisely utilizing Information Technology in the formulation of marketing strategies, organizations can achieve competitive advantage and improve their performance in an increasingly changing and competitive market.